2021
DOI: 10.1101/2021.09.14.460394
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-SARS-CoV-2 IgG and IgA antibodies in COVID-19 convalescent plasma do not facilitate antibody-dependent enhance of viral infection

Abstract: The novel coronavirus SARS-CoV2, which causes COVID-19, has resulted in the death of nearly 4 million people within the last 18 months. While preventive vaccination and monoclonal antibody therapies have been rapidly developed and deployed, early in the pandemic the use of COVID-19 convalescent plasma (CCP) was a common means of passive immunization, with the theoretical risk of antibody-dependent enhancement (ADE) of viral infection remaining undetermined. Though vaccines elicit a strong and protective immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…The titers of SARS-CoV-2 antibody measured indicates that most antibodies generated against S protein and N protein belonged to subtype IgG; there were only low levels of antibodies with subtype IgM (21). This is not surprising; IgG antibody is typically produced for several weeks and lasts for a long time (more than 13 weeks), whereas IgM antibody is transiently expressed (22).…”
Section: Discussionmentioning
confidence: 99%
“…The titers of SARS-CoV-2 antibody measured indicates that most antibodies generated against S protein and N protein belonged to subtype IgG; there were only low levels of antibodies with subtype IgM (21). This is not surprising; IgG antibody is typically produced for several weeks and lasts for a long time (more than 13 weeks), whereas IgM antibody is transiently expressed (22).…”
Section: Discussionmentioning
confidence: 99%
“…In the early phase of the COVID-19 epidemic, transfusion of convalescent plasma from acute coronavirus infection was reported as an effective treatment for severe patients (32). Some studies demonstrated that the response of antibodies to the RBD of the spike protein was highly correlated with neutralization of SARS-CoV-2 (33,34).…”
Section: Sars-cov-2 (19)mentioning
confidence: 99%
“…Na kanwie rozważań o ADE pojawia się również pytanie, czy terapia surowicą ozdrowieńców lub wyprodukowane przeciwciała są i do którego dnia mogą być skuteczne, co znajduje odzwierciedlenie w publikacjach. W tym aspekcie przeważają jednak doniesienia o tym, że takie zjawisko, jak ADE nawet w czasie choroby nie występuje [27,28]. Od początku logiczne wydawało się, że surowica ozdrowieńców może być skuteczna, jeśli zastosuje się ją bardzo wcześnie (dopóki istnieją wiriony, a nie ich remnanty), co okazało się być nierealne w warunkach szpitalnych.…”
Section: Adres Do Korespondencjiunclassified